ASUHAN KEPERAWATAN KELUARGA PADA PASIEN HIPERTENSI DENGAN PEMBERIAN TERAPI RENDAM KAKI AIR JAHE HANGAT UNTUK MENURUNKAN TEKANAN DARAH DI WILAYAH KERJA PUSKESMAS SUNGAI PANAS KOTA BATAM - Ari Anggara; Resi Novia (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2026)
Abstract: Hypertension is a condition characterized by persistent blood pressure with systolic ≥140 mmHg and diastolic ≥90 mmHg. Family support plays an important role in managing hypertension to prevent complications. This study aims to provide family nursing care to a patient with hypertension through warm ginger foot soak therapy to reduce blood pressure.This study used a descriptive case study design conducted from August 3 to August 8, 2025. Data were collected through assessment, diagnosis, intervention, implementation, and evaluation. The main nursing diagnosis identified was ineffective health management.The intervention provided was warm ginger foot soak therapy for 15–20 minutes, conducted over five days. The results showed a decrease in blood pressure from 170/110 mmHg to 120/90 mmHg.It can be concluded that warm ginger foot soak therapy is effective as a non-pharmacological intervention to reduce blood pressure in patients with hypertension.